Engineering Emotional Intelligence in Moroccan Primary School - Muftisada Jaouad; Mustapha Bassiri; Malika Tridane; Said Belaaouad (Iraqi Journal of Science, 2021)
The Moroccan socio-economic context is more and more weakened by a dynamic of accelerated measures aimed at redressing the financial deficits of the state. The first emotionally impacted by this dynamic are parents and therefore their children who begin to live in a universe dominated by fluctuations and unforeseen events.This article will therefore explore the emotional situation of Moroccan pupils at the beginning of schooling and identify their needs in this area, in order to initiate a dynamic of engineering emotional intelligence in primary school.The study was carried out in 3 school groups in Casablanca on a mixed population of 160 pupils and was spread out over a month. The used tools comprised interviews with survey filling to measure the degree of awareness of emotions on the part of these pupils and their teachers. Subsequently, the population was subjected to two tests respectively of impulses control and team spirit.The results show an initial dominance of emotions in the studied population and demonstrate the major interest of a gradual integration of emotional intelligence courses in the primary cycle of education.